2011
DOI: 10.1016/j.humov.2010.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Haptics in teaching handwriting: The role of perceptual and visuo-motor skills

Abstract: Two studies were carried out in order to better understand the role of perceptual and visuo-motor skills in handwriting. Two training programs, visual-haptic (VH) and visual (V), were compared which differed in the way children explored the letters. The results revealed that improvements of VH training on letter recognition and handwriting quality were higher than improvements after V training. We suppose that VH training was more efficient because it improved both perceptual and visuo-motor skills. In the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 57 publications
6
74
0
5
Order By: Relevance
“…However, the ability to recognize the visual-auditory associations was better after the multisensory method than after the classic one. The advantage of a visuo-haptic training over a visual training was also demonstrated in kindergarten children for letter recognition, handwriting quality (Bara & Gentaz, 2011) and geometry (Pinet & Gentaz, 2008). If children presenting low visuo-spatial abilities were able to acquire a haptic sense of numbers (as observed in individuals with blindness), promoting a (visuo-) haptic teaching of arithmetic could probably boost the development of their numerical competencies.…”
Section: Ws • Global Spatial Deficitmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the ability to recognize the visual-auditory associations was better after the multisensory method than after the classic one. The advantage of a visuo-haptic training over a visual training was also demonstrated in kindergarten children for letter recognition, handwriting quality (Bara & Gentaz, 2011) and geometry (Pinet & Gentaz, 2008). If children presenting low visuo-spatial abilities were able to acquire a haptic sense of numbers (as observed in individuals with blindness), promoting a (visuo-) haptic teaching of arithmetic could probably boost the development of their numerical competencies.…”
Section: Ws • Global Spatial Deficitmentioning
confidence: 87%
“…Continuing to study this question is particularly important given the good numerical abilities demonstrated by the individuals with blindness. In line with the theories of embodied cognition, some studies already demonstrated that the addition of the visuo-haptic exploration could help healthy adults to learn some abstract concepts more effectively (Bara & Gentaz, 2011;Fredembach, Hillairet de Boisferon, & Gentaz, 2009;Pinet & Gentaz, 2008). In the study of Fredembach and colleagues (2009), adults were asked to learn 15 new arbitrary associations between visual stimuli and their corresponding sounds using two learning methods which differed according to the perceptual modalities involved in the exploration of the visual stimuli.…”
Section: Ws • Global Spatial Deficitmentioning
confidence: 96%
“…Si de plus en plus de recherches portent sur le développement des processus impliqués dans l'écriture Zesiger, Deonna et Mayor, 2000), rares encore sont celles qui s'intéressent à un effet d'apprentissage ou d'entrainement (Bara et Gentaz, 2011;Morin et Montési-nos-Gelet, 2007). Par conséquent, le cadre théorique s'attachera à mettre en exergue ces dernières.…”
Section: Discussionunclassified
“…ACM 978-1-4503-3314-6/14/11$15.00 http://dx.doi.org/10.1145/2693787. 2693805 Digital handwriting technology has already been successfully applied in educational settings [2,4,18]. For example, introducing haptic feedback during handwriting has been found to improve letter recognition and phonological awareness in children [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…2693805 Digital handwriting technology has already been successfully applied in educational settings [2,4,18]. For example, introducing haptic feedback during handwriting has been found to improve letter recognition and phonological awareness in children [2,15]. Furthermore, studies have investigated using digital writing tools with handwriting recognition software for text entry and digitisation [17,18,20].…”
Section: Introductionmentioning
confidence: 99%